Sanitation practices and circular pathways in the Upper West Region of Ghana - Gebrezgabher, Solomie A.; Dongzagla, A.; Joshi, Deepa; Nicol, Alan (International Water Management Institute, 2024)
The United Nations’ Sustainable Development Goals (SDGs) aim to achieve safely managed sanitation for all by the year 2030. However, access to safely managed sanitation in Ghana remains low. In 2022, the Joint Monitoring Programme (JMP)1 estimated that access to safe sanitation in Ghana was less than 16%, with approximately 17.2% of the population still practicing open defecation. While modest progress has been made in the provision of sanitation facilities in Ghana, progress remains uneven across the value chain. As part of the Towards Brown Gold project, the International Water Management Institute (IWMI) analyzed current sanitation practices in Wa, a rapidly urbanizing small town in the Upper West Region of Ghana, to gain insights into sanitation systems from the perspective of local communities. The study also explored cultural and social attitudes toward fecal sludge management (FSM) and identified potential circular pathways for improving FSM.